O uso de tecnologias digitais de informação e comunicação no ensino de química: análise dos desafios e das possibilidades na pós-pandemia da Covid-19 em Macapá/AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
The Covid-19 pandemic brought a series of challenges and transformations that affected society in various areas, especially education. In this regard, it is worth highlighting the Chemistry curriculum component, an experimental and, in many cases, abstract science that, due to the suspension of in-person classes, was impacted in teaching by the inability to access laboratories and group practices that would facilitate student learning and, therefore, was taught entirely remotely. The mandatory and sudden use of Digital Information and Communication Technologies (DICT) during Emergency Remote Teaching (ERT), as an alternative practice to meet the need for continuity of education, raised several questions regarding infrastructure, teacher training, digital inequality, among others. Currently, in this post-pandemic period, it is not known whether these issues have been overcome, in addition to the emergence of other questions related to the continuity of teaching practices through the use of ICT, challenges for inclusion, resistance to change, and the applicability of ICT use in specific curricular components. In view of the above, the research problem was defined as: in what ways are the challenges and possibilities regarding the use of Information and Communication Technologies in Chemistry teaching in the post-Covid-19 pandemic period in Macapá/Ap presented? From this perspective, the main objective of the research was: to analyze the challenges and possibilities regarding the use of Information and Communication Technologies in Chemistry teaching in the post-Covid-19 pandemic period in Macapá/Ap. And as specific objectives, the following were outlined: to describe the educational context in the pandemic and post-pandemic scenario, focusing on teaching practices; to discuss the application of ICT resources used in education, as well as obstacles and challenges faced, in addition to the possibilities as a differential in the teaching process; to examine in the practices of Chemistry teachers how the use of Digital Information and Communication Technologies occurs in the post-Covid-19 pandemic. Regarding methodological aspects, the foundation was based on the Hermeneutic Dialectical method (Stein, 1983; Minayo, 1996), the research was qualitative in nature (Flick, 2009) and of the case study type (Yin, 2015). Data collection was carried out through the application of a semi-structured questionnaire (Gil, 2002) with five Chemistry teachers, whose research loci were the State School Professor Gabriel Almeida Café and the State School Mário Quirino da Silva. The data analysis was carried out with the support of Thematic Analysis (Braun; Clarke, 2006). The study highlighted the lack of training and institutional support as the main obstacles to the critical appropriation of ICTs in the educational context. Furthermore, it was observed that in the post-pandemic period, teachers' digital skills have evolved, and a new perspective of reconfiguring pedagogical thinking for the use of these tools has emerged. However, the use of technologies occurs partially, based on practices marked by individual use, meaning there is no standardization or policies promoting inclusion. Therefore, the actions carried out by each professional are constrained by limitations in infrastructure, training, and knowledge acquired during emergency remote teaching.
Keywords: Covid-19 - Pós-Pandemia; Ensino de Química; Tecnologias Digitais de Informação e Comunicação (TDIC); CNPQ::CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM:TECNOLOGIA EDUCACIONAL; ODS 4 – Educação de qualidade; ODS 9 – Indústria, inovação e infraestrutura; ODS 10 – Redução das desigualdades